Pengaruh Phubbing terhadap Interaksi Sosial Siswa Kelas X SMAN 3 Jember - Sofianta, Nurma (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2021)
The purpose of this study was to find out whether or not the influence of phubbing behavior on the social interaction of class X students in SMA N 3 Jember. The research method used is descriptive analysis correlation. The population used as objects in this study are students of class X SMA N 3 Jember in the 2019-2020 school year. The sample in this study were 170 students. The results of the study were calculated with the Pearson Product Moment Test, with a significance level of 5% and N 170 obtained r count of 0.306 and r table of 0.1497. After r count compared to r table it turns out that r count is greater than r table that is 0.306> 0.1497. thus it can be concluded that the hypothesis (ha: phubbing behavior influences the level of communication quality of class X students of SMA N 3 Jember can be accepted).